Application of indium tin oxide to the p‐cladding layers of yellow/green II‐VI compound semiconductor laser diode structures on InP substrates. Issue 7 (9th February 2016) - Fukushima, Koji; Shiraishi, Tomohiro; Kobayashi, Ryohei; Kishino, Katsumi; Nomura, Ichirou
Abstract: The application of indium tin oxide (ITO) as the p‐cladding layer of II‐VI compound semiconductor laser diodes (LDs) on InP substrates was investigated. The waveguide analysis of the LD structures revealed that the optical confinement effect around the active layer was obviously improved by changing the p‐cladding layer from the conventional MgSe/BeZnTe superlattice to ITO. For example, the estimated optical confinement factors were 0.15 and 0.27 for the conventional and ITO LD structure, respectively, when the emission wavelength was 580 nm. In addition, we investigated optimum LD structures, considering the optical and carrier confinements at the active layer. In experiments, light emitting devices with an ITO layer were fabricated on InP substrates via molecular beam epitaxy and radio‐frequency (RF) magnetron sputtering. Yellow emissions at 582 nm were observed by current injections at room temperature. These results indicate that ITO is a promising p‐cladding layer material for II‐VI LDs on InP substrates. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)